Analisis Hubungan Pertumbuhan Ekonomi, Angkatan Kerja dan Inflasi di Indonesia: Pendekatan Vector Error Correction Model (VECM) - Yolanda Sari; Etik Winarni; Muhammad Amali (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this research is to analyze the causality and long-term relationship between economic growth, labor force and inflation in Indonesia. This study uses secondary data obtained from the World Bank in the form of annual data with a quantitative descriptive approach using the Vector Error Correction Model (VECM). The results of the study showed that there was no causal relationship between the labor force and economic growth and there was no causal relationship between inflation and economic growth, but there was a one-way relationship between labour force and inflation, namely inflation affects the labor force. In the short term, there was none of the variable had a significant effect on economic growth. The labor force had a positive and insignificant impact on economic growth during 2000-2021 in the short term, while inflation had a negative and insignificant impact on economic growth in 2000-2021 in the short term, but in the long term inflation had a positive and significant impact.